University contributions to the circular economy: Professing the hidden curriculum - Nunes, Ben Tirone; Pollard, Simon J. T.; Burgess, Paul J.; Ellis, Gareth; de los Rios, Irel Carolina; Charnley, Fiona (MDPI, 2018)
In a world dominated by linear economic systems, the road to improving resource use is multi-faceted. Whilst public and private organisations are making progress in introducing sustainable practices, we ask ourselves the extent to which education providers are contributing to the circular economy. As engines for skills and knowledge, universities play a primary role in propelling circular economy approaches into reality and, as such, hold the potential for raising the bar on sustainable performance. A rapid evidence assessment (REA) was therefore undertaken to examine the interactions between university estate management and the circular economy. This assessment identified six pertinent themes: campus sustainability, the hidden curriculum, environmental governance, local impact, university material flows, and the role of universities as catalysts for business and examined 70 publications. A second part of the study reviewed the environmental activities of 50 universities ranked highly in terms of their environmental credentials or their environmental science courses. The results are presented and then discussed in terms of how universities can affect material flows, promote sustainability outside of the formal curriculum, and act as catalysts with business. The economic significance of universities provides an appreciable demand for circular products and services. Universities should develop “hidden curriculum” plans to promote improved environmental behaviours of staff and students. Universities can also catalyse a circular economy by working with business to improve eco-effectiveness as well as eco-efficiency. For example, projects should extend the focus from decreasing carbon footprint to achieving carbon positivity, from improving water efficiency to treating wastewater, and from recycling to reverse logistics for repurposing. Pilot projects arising from such work could provide valuable research bases and consultancy opportunities.
Keywords: Circular economy; Hidden curriculum; University estate; Material flow; Environmental management